O projeto da ditadura civil-militar para a Amazônia no pensamento de Arthur Reis e Meira Mattos (1964-1972) - Coelho, Wanderson de Oliveira (2019)
The central objective of this research was to reproduce and analyse, critically, the set of ideas elaborated by the historian Arthur Reis and the general Meira Mattos. For this purpose, besides probing the sense of the ensemble of each author’s individual work and the constitutive features of their theoretical perspectives as a whole, we have centralized the investigation in themes that translated better the dissertation’s finality. Thus, in first place, we have demarcated the inherent meaning of each author’s logic of thought itself, which was taken in its particularity. Simultaneously, we have kept track of the link of both with the conspiracy, the coup and the civil-military dictatorship of 1964, in its total meaning and, mainly, in what concerns the political-ideological field. In this sense, we appreciate the treatment each one gave to the Amazon question, a theme that occupied a prominent place in the set of works and received a special attention in the forwarding of the ditactorial government’s action project. The period in which Reis was governor coincided with the first military government, so that his political speeches were linked to the Castelo Branco presidency. In this context, we try to unveil the relationship between the author’s project and that of Dictatorship for the Amazon – both present in the set of speeches delivered – and analyse them in the light of the understanding of dictatorial interventions in Amazon. Lastly, we return our analysis to the way how Meira Mattos brought forward the political project of the dictatorial government of 1964, giving special attention to his geopolitical work and his role as an ideologist.